2022
DOI: 10.26434/chemrxiv-2022-xndvx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potential-dependent Pt(111)—water interface: Tackling the challenge of a consistent treatment of electrochemical interfaces

Abstract: The interface between an electrode and an electrolyte is the location where electro- chemical processes for countless technologically important applications occur. Though its high relevance and the intense efforts devoted to its elucidation, an atomic-level description of the interfacial structure and especially the dynamics of the electric double layer is still amiss. Here, we present reactive force field molecular dynamics simulations of electrified Pt(111)|water interfaces, shedding light on the orientation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Theory and experiment revealed that the pushback effect of adsorbed hydrogen decreases the work function of Pt(111) ( Li et al, 2021 ), whereas the pullout effect of adsorbed oxygen increases it ( Malek and Eikerling, 2018 ). As regards the EDL at Pt(111) contacted with an acidic aqueous solution, a mean-field model has shown that chemisorption of partially charged hydroxyl and oxygen contributes an additional surface dipole moment, leading to a second pzc and an overall nonmonotonic surface charging behavior ( Huang et al, 2016 ; Huang et al, 2018 ), which are confirmed in atomistic simulations ( Fernandez-Alvarez and Eikerling, 2019 ; Tesch et al, 2021 ; Braunwarth et al, 2022 ).…”
mentioning
confidence: 73%
“…Theory and experiment revealed that the pushback effect of adsorbed hydrogen decreases the work function of Pt(111) ( Li et al, 2021 ), whereas the pullout effect of adsorbed oxygen increases it ( Malek and Eikerling, 2018 ). As regards the EDL at Pt(111) contacted with an acidic aqueous solution, a mean-field model has shown that chemisorption of partially charged hydroxyl and oxygen contributes an additional surface dipole moment, leading to a second pzc and an overall nonmonotonic surface charging behavior ( Huang et al, 2016 ; Huang et al, 2018 ), which are confirmed in atomistic simulations ( Fernandez-Alvarez and Eikerling, 2019 ; Tesch et al, 2021 ; Braunwarth et al, 2022 ).…”
mentioning
confidence: 73%
“…Le et al showed that the density of H ad peaks at ∼1 Å above the metal surface . Braunwarth et al gave a bond length of 1.05 Å for adsorbed O on Pt(111) . Therefore, I use δ 1 = 1 A ̊ for the AIP.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Adsorbed ions, if any, are usually located closer to the metal surface than adsorbed solvent molecules, according to atomistic simulations, e.g. , by Braunwarth et al 83 The central plane of adsorbed ions is denoted AIP. Different characteristic planes are used for depicting the ASP and AIP due to difference between ionic charge and dipolar charge.…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 2 more Smart Citations